Self-Empowerment and Academic Success: CliftonStrengths in Doctor of Physical Therapy Students - Disney, Heather; San Lucas, Summer (Journal of Teaching and Learning, 2026)
Leadership is vital in healthcare, improving patient care through quality, safety, and accountability. This study aimed to identify common CliftonStrengths themes among Doctor of Physical Therapy (DPT) students, to explore correlations with GPA, and to assess students' perceptions of their strengths. A retrospective, mixed-methods study was conducted with 121 DPT students. CliftonStrengths assessments were administered, and quantitative data were analyzed for common strengths and GPA correlations. Qualitative data explored student perceptions. The most common strengths were Restorative, Achiever, Relator, Learner, and Harmony. Command, Context, Maximizer, and Self-assurance were the least common. Relationship-building was the most frequent domain, influencing the least. No significant correlation was found between strengths domains and GPA, though students in the Executing domain had the highest average GPA (3.41) and those in Influencing the lowest (3.04). Findings align with those of other healthcare studies, in which Learner, Relator, and Achiever are common strengths. Qualitative analysis revealed increased self-awareness and empowerment when reflecting on their identified strengths. Incorporating strengths-based assessments such as CliftonStrengths fosters leadership development among DPT students, aligns with the APTA’s vision, and prepares future therapists for effective patient care.